Psychosocial response to the COVID-19 pandemic in Panama - Diana C. Oviedo; Diana C. Oviedo; Diana C. Oviedo; María Sofía Pinzón; Sofía Rodríguez-Araña; Adam E. Tratner; Elianne Pauli-Quirós; Carlos Chavarría; Camilo Posada Rodríguez; Gabrielle B. Britton; Gabrielle B. Britton (Frontiers Media S.A., 2022)
BackgroundThe impact of the COVID-19 pandemic and the associated restrictions on mental health is being studied.ObjectiveTo analyze the psychosocial response to the COVID-19 pandemic in adults residing in Panama.MethodsA community sample of 480 adult residents of Panama completed a survey that included sociodemographic questions, COVID-19 related questions (e.g., health concerns regarding the virus, knowledge and behaviors in biosafety) and scales of stress, anxiety, depression, prosocial behavior, resilience, perceived social support, and insomnia.ResultsMost of the participants (>60%) reported being negatively affected by the pandemic. Women experienced greater depression, anxiety, and stress symptoms than men, and age was negatively associated with depression, anxiety, and stress symptoms. Self-perceived health status and self-perceived social support were negatively associated with depression, anxiety, and stress symptoms. Self-perceived social isolation was positively associated with depression, anxiety, and stress symptoms. Psychiatric illness and insomnia were positively associated with depression, anxiety, and stress symptoms, whereas psychological resilience was negatively associated with depression, anxiety, and stress symptoms.DiscussionThese results corroborate other studies regarding COVID-19 and mental health. This study highlights the need for specific prevention and intervention mechanisms related to the COVID-19 pandemic in different population groups. This is the first report of the psychological impact of COVID-19 in the general Panamanian population and one of the only studies in the Latin American region and, therefore, contributes to research in the Latino population and lower-middle income countries.